Making growth more inclusive in Costa Rica - González Pandiella, Alberto (OECD Economics Department Working Papers, 2016)
In the past 30 years Costa Rica has grown steadily and social indicators have improved markedly. Well-being indicators are comparable or even above the OECD average in several dimensions, such as health, environment or life-satisfaction. This paper reviews the social progress that Costa Rica has achieved and identifies reducing inequality and poverty as the main challenges. To tackle those challenges, the paper argues that there is a need to upgrade existing social assistance programmes to maximise their impact. Social policies should put more emphasis on getting more people into formal work, including by raising their skill levels. This is the most effective way to get people out of poverty. Education is the area where the largest gap with respect to OECD countries is observed. Policy efforts are also warranted to tackle informality, which is increasing rapidly, and to close the gender gap in the labour market. The health and pension systems play a fundamental role in maintaining social cohesion in Costa Rica and it is crucial to modernise them and to make them sustainable in the face of demographic challenges. Costa Rica exemplifies the benefits of preserving natural resources in generating growth and employment opportunities, thereby providing a way out of poverty. Building on its achievements in this area, Costa Rica should reinforce environmental protection efforts, such as reducing emissions from the transport sector and improving wastewater treatment